The Gravity of Objects: How Affectively Organized Generative Models Influence Perception and Social Behavior - Connolly, Patrick (Frontiers in Psychology, 2019)
Friston’s (2010) Free Energy Principle (FEP) offers an opportunity to rethink what is meant by the psychoanalytic concept of an object, or discrete mental representation (Ogden, 1992). The significance of such objects in psychoanalysis is that they may be superimposed on current experience so that perceptions are partly composed of projected fantasy, and partly of more realistic perception. From a free energy perspective, the psychoanalytic (person) object may be understood as a bounded set of prior beliefs about a ‘platonic’ sort of person, that provides a free energy minimising, evidence maximising, hypothesis to explain inference about – or dyadic interactions with – another. The degree to which realistic perception supervenes - relative to a platonic person object - will depend upon the precision assigned to the sensory evidence (concerning the person) relative to the prior beliefs about a platonic form. This not only provides a basis for explaining projection and transference phenomena, but also for conceptualizing a central assumption within object relations psychoanalysis. As an example, the paper examines the Kleinian theory of split good or bad part-objects as affectively-organized generative models (or platonic part-object models) formed in early infancy. This also provides a basis for building on work by Kernberg (1984, 1996) by conceptualizing the role of the part-object(s) in a continuum of reality testing, from mild errors in perception that are relatively easily corrected, through borderline affective instability and frequent shifts between part-object experience, to psychotic failures of reality testing, where Friston, Brown, Siemerkus & Stephan (2016) propose that aberrant precisions bias perception to high precision false beliefs (here cast as platonic part-objects), such as stable perceptions of others (and possibly oneself) as persecutory agents of some sort. The paper demonstrates the value that the history of clinical insights in psychoanalysis (including object relations) and a systems-based approach to the brain (including the free energy principle) can have for one another. This is offered as a demonstration of the potential value of an ‘Integrative Clinical Systems Psychology’ proposed by Tretter and Lӧffler-Stastka (2018) which has the potential to integrate the major theoretical frameworks in the field today.